Line plots of ||. - Maryam Arianpouya (12299222) (2024)
The plots are taken horizontally through a plane intersecting the wire location, as represented by the |B1+| maps for CH1-CH4 as shown in Fig 3C. The artifact (normalized to the maximum value observed across channels) surrounding the wire tip is much larger for CH1 and CH4 (elements closer to the wire) than for CH2 and CH3 (elements further from the wire).